THE EFFECTIVENESS OF ARIAS LEARNING MODEL ASSISTED AUDIOVISUAL MEDIA IMPROVING LEARNING OUTCOMES - Molla, Nur Laila; Sucipto, Muhammad Arif Budiman (Universitas Kuningan, 2019)
ARIAS learning model instills confidence, relevance, interest, attention, and evaluation to find out success and pride in the results of achievement. With the help of audiovisual media, it will further enhance students' interest, attention, and activeness. Research Objectives 1) finding out differences in learning outcomes of significant ARIAS learning model with audiovisual media and conventional learning models. 2) Determining effectiveness of using ARIAS Learning Model assisted by audiovisual assisted audiovisual media in improving learning outcomes with conventional learning models. Quantitative research is a true design experiment. Design used was a pretest-posttest control group design. The population is all the third-semester students majoring in economics. Sample by means of non probability sampling with a purposive sampling technique, Data analysis techniques use independent test t-test and paired test. Results of independent test t test obtained t count = 3.375 with sig (2tailed) = 0.001 0.05 which means a significant difference in learning outcomes between ARIAS learning model with conventional learning models. Paired test results obtained a value of t count of -20,378 with the sig. (2-tailed) = 0.00 0.05 which means an increase in learning outcomes between ARIAS learning models with conventional models. The results obtain of average pre-test is 56.07 and post-test is 79.97. Furthermore, the conclusion is Arias assisted audiovisual learning model effectively improved learning outcomes of English subjects.